2020
DOI: 10.1016/j.rasd.2020.101680
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a novel caregiver-report tool to assess barriers to physical healthcare for people on the autism spectrum

Abstract: Highlights A novel caregiver-report Barriers to Healthcare tool for autistic individuals was developed and evaluated. Results suggest that barriers to healthcare occur at the patient, healthcare-provider and systems levels. Autism severity, anxiety, general adjustment problems, age, and having unmet needs significantly predicted barriers endorsed. This tool may guide the development and evaluation of initiatives to reduce healthcare barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…GP General practitioner congruent with current understandings of barriers to access by autistic patients and their caregivers [26,66], and may be considered to supplement existing tools for caregivers [31] and autistic adults [26]. It must be noted that there is some convergence between items in the current tool and those of previously reported tools which assess barriers to healthcare for autistic patients (e.g., [13,33,61,67]).…”
Section: Phase 1 Tool Development and Evaluationmentioning
confidence: 80%
See 2 more Smart Citations
“…GP General practitioner congruent with current understandings of barriers to access by autistic patients and their caregivers [26,66], and may be considered to supplement existing tools for caregivers [31] and autistic adults [26]. It must be noted that there is some convergence between items in the current tool and those of previously reported tools which assess barriers to healthcare for autistic patients (e.g., [13,33,61,67]).…”
Section: Phase 1 Tool Development and Evaluationmentioning
confidence: 80%
“…In order to ensure that this is the case, the specific difficulties physicians face when caring for their autistic patients first need to be understood. Although measures exist to facilitate exploration of healthcare-associated barriers among autistic adults [26], or the caregivers of autistic individuals [31], there is a lack of established methods for engaging staff about their experiences and perceptions. A number of previous studies have used HCP-reported measurement tools to assess barriers to providing healthcare to autistic individuals, however, they are typically limited in the array of barriers that they assess (e.g., [32][33][34]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true given that none of the included studies employed a full randomized controlled trial design (two studies employed randomization but were described as pilot studies) which continues to constitute the "gold standard" for interventional research and to afford the most trustworthy evidence on effectiveness (Bothwell et al, 2016;Hariton & Locascio, 2018). However, research has now effectively delineated the barriers to healthcare access (Calleja et al, 2020;Mason et al, 2019;Walsh et al, 2020a), and there exist a number of tools to facilitate data collection in relation to the barriers to healthcare access experienced by autistic adults (Nicolaidis et al, 2013) or the caregivers of autistic persons (Walsh et al, 2020b) or healthcare providers (Walsh et al, 2021) which should facilitate future research in this area. This research must move beyond developing understanding on, and collecting data relating to experiences of, healthcare access and experiences of autistic persons to "actioning" data to inform the development and implementation of interventions to improve the care and health of autistic persons.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers, or quality professionals, may wish to use existing tools to establish the barriers to care in advance of intervention development to ensure that interventions are likely to yield perceptible improvements for autistic patients. For example, Raymaker and colleagues (2017) have developed a tool that allows autistic individuals to self-report barriers experienced in healthcare settings, Walsh et al (2020b) present a tool which allows the caregivers of autistic patients to report on the frequency and severity of barriers experienced in physical healthcare settings, and Walsh et al (2021) have completed initial validation of a tool which allows healthcare providers to identify barriers to care provision or access for autistic patients. The use of such tools will allow providers or organizations to determine the most frequent (and in some instances, the most severe) barriers impacting care for autistic patients within their organization or setting.…”
Section: Discussionmentioning
confidence: 99%